2004
DOI: 10.1097/01.ju.0000104561.90514.cb
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Augmentation Cystoplasty on Bone Metabolism in Chronic Uremic Rats

Abstract: Our results suggest that cystoplasty using ileum segments can aggravate renal bone disease in growing rats with mild uremia. Since the acid-base state was unchanged, other properties of the interposed ileum segment must be responsible for the negative effect on bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In this study, augmented animals, which developed metabolic acidosis, had shorter femur lengths than controls and whole body BMD was decreased. Brkovic et al [21] reported the DEXA results of uremic rats, which underwent augmentation cystoplasty with stomach, ileum, and sigmoid colon. Mean BMD values of augmented rats were lower than the control group, even though pH values of each group were within the physiological range.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, augmented animals, which developed metabolic acidosis, had shorter femur lengths than controls and whole body BMD was decreased. Brkovic et al [21] reported the DEXA results of uremic rats, which underwent augmentation cystoplasty with stomach, ileum, and sigmoid colon. Mean BMD values of augmented rats were lower than the control group, even though pH values of each group were within the physiological range.…”
Section: Discussionmentioning
confidence: 98%
“…Although almost all the clinical and experimental studies [18,19,[21][22][23] did the bone density measurement at the spine, we also included femoral neck BMD measurements to compare the neurogenic and non-neurogenic groups. The femoral neck BMD decreased 28% in neurogenic group and 13.8% in non-neurogenic group, when compared to age-and sex-matched population [24].…”
Section: Discussionmentioning
confidence: 99%
“…Animals were randomly allocated to receive weekly subcutaneous injections of either vehicle (0.9% saline) or ibandronate (Bondronate; Roche Diagnostics, Mannheim, Germany; 1.25 μg/kg body weight) for a total of 10 weeks. This dosage was selected since it was shown to be well tolerated in uremic rats and can be given once weekly [17,20,21]. Four groups were included in the study: (1) vehicle-treated, sham-operated rats; (2) ibandronate-treated, sham-operated rats; (3) vehicle-treated CRF rats; (4) ibandronate-treated CRF rats.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…The impact of urinary diversion using several types of intestinal segments on the bone metabolism of growing rats with renal insufficiency was examined by Brkovic et al [30]. Uremic rats underwent enterocystoplasty using stomach, ileum, or colon.…”
Section: Preclinical Evidence For Differing Renal Safety Profilesmentioning
confidence: 99%